Dual‐Hole Excitons Activated Photoelectrolysis in Neutral Solution. Issue 14 (19th February 2018) - Hung, Sung‐Fu; Chen, Zhi‐Zhong; Chang, Chun‐Chih; Hsu, Chia‐Shuo; Tsai, Ming‐Kang; Kang, Chia‐Cheng; Chen, Hao Ming
Abstract: II–VI semiconductors exhibit unique behaviors that can generate dual‐holes ("heavy and light"), but the application in photocatalysis is still missing. Herein, an empirical utilization of light/heavy holes in a hybrid metal cluster‐2D semiconductor nanoplatelets is reported. This hybrid material can boost the hole‐transfer at the surface and suppress the recombination. Different roles are enacted by light‐holes and heavy‐holes, in which the light‐holes with higher energy and mobility can facilitate the slow kinetics of water oxidation and further reduce the onset voltage, while the massive heavy‐holes can increase the resulting photocurrent by about five times, achieving a photocurrent of 2 mA cm −2 at 1.23 V versus RHE under AM 1.5 G illumination in nonsacrificial neutral solution. These strategies can be the solutions for photoelectrolysis and be beneficial for sustainable development in solar conversion. Abstract : Dual‐holes system spontaneously activates the surface of photocatalyst and leads massive holes pass through the activated surface; furthermore, the hybrid metal facilitates the spatial charge separation. This design achieves a highly efficient photoelectrochemical device in neutral electrolyte.